Antibiotic resistance of Helicobacter pylori in Mongolia - Bolor-Erdene, Mandkhai; Namdag, Bira; Yamaoka, Yoshio; Jav, Sarantuya (The Journal of Infection in Developing Countries, 2017)
Introduction.The resistance of Helicobacter pylori to recently available antibiotic treatment regimens has been recognized as a growing problem. Therefore, the aim of this study was to determine the prevalence of antibiotic resistance among H. pylori strains isolated from Mongolians. Methodology. All gastric biopsy specimens were obtained during upper gastrointestinal endoscopy from patients referred for the exploration of dyspepsia. The urease positive samples by rapid urease test were cultured according to standard microbiological procedures and H. pylori were grown under microaerophilic conditions on selective Pylori agar. H. pylori antibiotic sensitivity was examined using E-test. In addition, the mutations of the corresponding gene were studied by GenoType HelicoDR DNA strip testing. Results. Three hundred twenty patients, 216 female and 104 male in the ages range of 18 to 83 years were included in this study. Rapid urease test yielded positive results for 65.9% (211/320). Among them, we have successfully obtained 72% H. pylori isolates. The antibiotic resistance rates were 35.5% for clarithromycin, 68.4% metronidazole, 23.0% amoxicillin, 25.0% tetracycline, 28.2% erythromycin and 14.5% nitrofuranton. Resistance for 2 drugs was 34.5% and that of 3 drugs was observed in 14.5% of isolates. The most prevalent mutation was A2147G followed by A2146G and D91Y. The prevalence of H. pylori infection increased among Mongolian population and the prevalence of resistance of H. pylori is very high to metronidazole, and moderate to clarithromycin. Conclusion. The data on antimicrobial susceptibilities provided by the present study is may assist the clinicians on the effectiveness of treatment regimens.